Effects of vildagliptin as add-on treatment in patients with type 2 diabetes mellitus: insights from long-term clinical studies in Japan - Odawara, Masato (J Diabetes Metab Disord, 2016)
BACKGROUND: Vildagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, is wildly used to treat type 2 diabetes mellitus (T2DM) with mono- or combination-therapy. We review two previously published open-label studies to extract insights on the long-term efficacy and safety of vildagliptin. METHODS: Two studies were conducted in Japan to assess the efficacy and safety of vildagliptin as an add-on to other oral antidiabetes drugs (OADs) for 52 weeks. These studies were performed under the similar protocol in Japanese patients with T2DM who were inadequately controlled with OAD monotherapy [excluding other dipeptidyl peptidase-4 (DPP-4) inhibitors]. RESULTS: Addition of vildagliptin (50 mg twice daily) to other OAD monotherapy [sulfonylurea (SU), metformin, thiazolidinedione, alpha-glucosidase inhibitor and glinide] reduced glycated hemoglobin (HbA1c) levels by −0.64 %,−0.75 %,−0.92 %,−0.94 % and − 0.64 %, respectively, over 52 weeks of treatment. Overall, the incidence of hypoglycemia was low and was slightly higher in the add-on to SU treatment group compared with the other groups. The incidences of adverse events were comparable among the treatment groups, and vildagliptin was well-tolerated as add-on therapy to other OADs. CONCLUSIONS: The evidence from the two studies indicates that vildagliptin as an add-on therapy to other OADs is a clinically reasonable option for Japanese patients with T2DM who respond inadequately to other OAD monotherapy.